Delimiting cryptic pathogen species causing apple Valsa canker with multilocus data. Issue 8 (19th March 2014) - Wang, Xuli; Zang, Rui; Yin, Zhiyuan; Kang, Zhensheng; Huang, Lili
Abstract Fungal diseases are posing tremendous threats to global economy and food safety. Among them, Valsa canker, caused by fungi of Valsa and their Cytospora anamorphs, has been a serious threat to fruit and forest trees and is one of the most destructive diseases of apple in East Asia, particularly. Accurate and robust delimitation of pathogen species is not only essential for the development of effective disease control programs, but also will advance our understanding of the emergence of plant diseases. However, species delimitation is especially difficult in Valsa because of the high variability of morphological traits and in many cases the lack of the teleomorph. In this study, we delimitated species boundary for pathogens causing apple Valsa canker with a multifaceted approach. Based on three independent loci, the internal transcribed spacer (ITS), β‐tubulin (Btu), and translation elongation factor‐1 alpha (EF1α), we inferred gene trees with both maximum likelihood and Bayesian methods, estimated species tree with Bayesian multispecies coalescent approaches, and validated species tree with Bayesian species delimitation. Through divergence time estimation and ancestral host reconstruction, we tested the possible underlying mechanisms for fungal speciation and host‐range change. Our results proved that two varieties of the former morphological species V. mali represented two distinct species, V. mali and V. pyri, which diverged about 5 million years ago, much later than the divergence of their preferred hosts, excluding a scenario of fungi–host co‐speciation. The marked different thermal preferences and contrasting pathogenicity in cross‐inoculation suggest ecological divergences between the two species. Apple was the most likely ancestral host for both V. mali and V. pyri. Host‐range expansion led to the occurrence of V. pyri on both pear and apple. Our results also represent an example in which ITS data might underestimate species diversity.